Relighting with real incident light source - Yifan Chen; Xubo Yang; Shuangjiu Xiao; Xiaodong Ding (2008 7th IEEE International Symposium on Mixed and Augmented Reality, 2008)
This paper presents an approach that can relight captured image with real incident light source. We first captured basis images of objects illuminated with a projector as the basis light source. We then established a pixel level mapping relationship between a real incident light source and the basis light source. Finally we developed a relighting algorithm that can simulate the relit effects with the real light source. The techniques can be applied to mixed reality.